Neotropical swarm-founding wasps (Vespidae: Polistinae: Epiponini) accept expelled queens in case of queen loss - Chavarria-Pizarro, L.; Silva, M. [UNESP]; Noll, F. B. [UNESP] (Universidade Estadual de Feira de Santana, 2018)
In the Epiponini, queen number declines through colony cycle, because some queens are expelled from colonies. Here we demonstrate that Epiponini wasps may accept expelled queens in situations of queenlessness. One colony of Protopolybia exigua was observed at the University of São Paulo in Brazil; and another of Metapolybia docilis was observed at La Selva Biological Station in Costa Rica. Queen removal tests were performed to study workers’ acceptance of expelled queens and queens from other colonies. In P. exigua, the experimental queen elimination caused a change in the workers’ behavior, ranging from aggressive expulsion of non-selected queens to re-acceptance. In M. docilis workers were willing to accept queens from other colonies after queen elimination. Our results indicate that because of a decrease in workers aggressiveness during the colony cycle, workers may accept expelled queens (even foreign ones, in experimental situations) in order to ensure colony survival.
Keywords: Behavior; Flexibility; Queen elimination; Queen selection